2017
DOI: 10.3390/ma10091018
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Electron Beam Irradiated Bacterial Cellulose Membranes as Compared with Collagen Membranes on Guided Bone Regeneration in Peri-Implant Bone Defects

Abstract: Bacterial cellulose (BC) is a natural polysaccharide produced by some bacteria, and consists of a linear polymer linked by β-(1,4) glycosidic bonds. BC has been developed as a material for tissue regeneration purposes. This study was conducted to evaluate the efficacy of resorbable electron beam irradiated BC membranes (EI-BCMs) for guided bone regeneration (GBR). The electron beam irradiation (EI) was introduced to control the biodegradability of BC for dental applications. EI-BCMs had higher porosity than co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…On the other hand, upon PRGF treatment, the changes of Young modulus values could be correlated with the ultrastructural properties of each membrane type, especially the porosity. The higher the porosity, the lower the Young modulus value obtained, which is consistent with similar results previously reported in literature [25]. This is also the reason why, after PRGF treatment, the Young modulus values are displayed in a narrow interval (2.8-4 GPa), compared with the corresponding values before treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, upon PRGF treatment, the changes of Young modulus values could be correlated with the ultrastructural properties of each membrane type, especially the porosity. The higher the porosity, the lower the Young modulus value obtained, which is consistent with similar results previously reported in literature [25]. This is also the reason why, after PRGF treatment, the Young modulus values are displayed in a narrow interval (2.8-4 GPa), compared with the corresponding values before treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Due to their advantages in terms of their different degrees of biodegradability, resorbable membranes, especially collagen-type, are the most popular in the field of dentistry, maxillo-facial surgery, or regeneration medicine [25]. It is very difficult to compare collagen membranes in terms of their resorbability and biodegradability based exclusively on the information reported in their datasheets, as it refers to different processing conditions and provenience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of technical approaches have been applied for scaffold production. In these cases, scaffolds should not only be a substitute of the extracellular matrix but also act as a membrane able to act as a delivery vehicle for cells and/or to serve as a carrier for growth factors [5,[66][67][68][69][70][71][72]. The final focus is the same: to engineer membranes with adequate properties able to improve interactions with the cells and to enhance tissue regeneration.…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…Several radiation-based techniques based on gamma ray, electron beam, or ion beam irradiation have been used to crosslink, graft, or degrade polymers and thus modify their properties [ 37 ]. In particular, it has been reported that high energy EI effectively reduces natural polymer molecular weight and mechanical properties without the need for additional chemicals [ 38 , 39 , 40 , 41 ]. The purpose of this study was to prepare BCMs irradiated with different electron beam doses and to determine their mechanical, chemical, and biological properties.…”
Section: Introductionmentioning
confidence: 99%